NON ALCOHOLIC STEATOHEPATITIS (NASH) EXPERIMENTAL MODEL INDUCTION IN RATS - SURAPANENI KRISHNA MOHAN,; SARASWATHI. P,; MALLIKA JAINU, (International Journal of Pharma and Bio Sciences, 2012)
Non Alcoholic steatohepatitis (NASH) is a silent asymptomatic disease which progress towards the fibrosis and cirrhosis, an end stage liver disease. Liver biopsy is the only method to confirm the diagnosis of NASH and is considered gold standard to confirm NASH. Liver biopsy is an invasive procedure and associated with many risks and this feature hinders to conduct studies in NASH in human beings. The development of an experimental NASH model in rats, which mimics human NASH is very much needed to conduct the studies related to the diagnosis and treatment strategies. Male Wister rats were divided into three groups as Group A, B & C treated with new experimental dose and for various periods such as 4 weeks, 8 weeks and 12 weeks. A portion of the liver tissue was taken after 4, 8, 12 weeks and its histological features were studied. Rats fed with high fat diet for 8 weeks showed diffused fatty Infiltration of hepatocytes with mono nuclear inflammatory infiltrate, confirming the development of NASH. A high-fat diet (HFD) is used to create a new experimental model of NASH and NASH has been successfully developed in the rats fed with high fat diet for 8 weeks. Thus, this model mimics the most common features of NASH in humans and provides an ideal tool for further research in NASH.